2004
DOI: 10.1002/cne.20223
|View full text |Cite
|
Sign up to set email alerts
|

Active caspase‐3 expression during postnatal development of rat cerebellum is not systematically or consistently associated with apoptosis

Abstract: Development is a dynamic process that includes an intricate balance between an increase in cell mass and an elimination of excess or defective cells. Although caspases have been intimately linked to apoptotic events, there are a few reports suggesting that these cysteine proteases can influence the differentiation and proliferation of cells. Specifically, the active form of caspase-3, which has been classified as an executor of apoptosis, recently has been implicated in a nonapoptotic role in the regulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 48 publications
(59 reference statements)
4
43
0
Order By: Relevance
“…Although it has been suggested that the presence of cleaved caspase-3 represents a point of no return in the apoptotic pathway (Huppertz et al, 1999), this form of the enzyme has also been identified in cells that are not undergoing apoptosis (Oomman et al, 2004). We found that astrocytes throughout the spinal cord of both SNI and naive rats showed moderate to high levels of cleaved caspase-3, and a similar observation has been made in naive rat spinal cord in two previous studies (Martin and Liu, 2002;Hoang et al, 2003).…”
Section: Detection Of Apoptotic Cells With Antibody Against Cleaved Csupporting
confidence: 86%
“…Although it has been suggested that the presence of cleaved caspase-3 represents a point of no return in the apoptotic pathway (Huppertz et al, 1999), this form of the enzyme has also been identified in cells that are not undergoing apoptosis (Oomman et al, 2004). We found that astrocytes throughout the spinal cord of both SNI and naive rats showed moderate to high levels of cleaved caspase-3, and a similar observation has been made in naive rat spinal cord in two previous studies (Martin and Liu, 2002;Hoang et al, 2003).…”
Section: Detection Of Apoptotic Cells With Antibody Against Cleaved Csupporting
confidence: 86%
“…Although the preponderance of data has emerged from work in the immune system and peripheral organs, several studies have also suggested non-apoptotic roles of caspase-3 in the CNS. Under physiological conditions, caspase-3 has been implicated in neuronal cytoskeletal changes (Rohn et al, 2004), in synaptic remodeling (Dash et al, 2000;Shimohama et al, 2001), in neuronal survival associated with preconditioning (Garnier et al 2003;McLaughlin et al, 2003;Tanaka et al, 2004), in the differentiation of cerebellar Bergmann glial cells (Oomman et al, 2004(Oomman et al, , 2005(Oomman et al, , 2006, and as a marker of astroglial subpopulations (Noyan-Ashraf et al, 2005). Accordingly, following excitotoxic damage in the neonatal brain we have demonstrated that presence of cleaved caspase-3 in nitrated reactive astrocytes in the absence of cell death (Acarin et al, 2005).…”
Section: Introductionmentioning
confidence: 76%
“…In addition, caspase-3 activation and substrate cleavage has been reported in the absence of cell death in gerbil hypoxia (Garnier et al, 2004) and in ischemic tolerance where neuronal caspase-3 is essential for the neuroprotective effect of preconditioning (Garnier et al 2003;McLaughlin et al, 2003;Tanaka et al, 2004). Furthermore, other studies have also demonstrated a role of caspase-3 in the maturation of cerebellar granular cells during development (Oomman et al, 2004) and the differentiation of neural progenitor cells in the olfactory bulb (Fernando et al, 2005;Yan et al, 2001). Progenitor cells that divide and migrate through the rostral migratory stream en route to the olfactory bulb, show cleaved caspase-3 but no signs of cell death (Yan et al, 2001).…”
Section: Presence Of Caspase-cleaved Gfapmentioning
confidence: 96%
See 1 more Smart Citation
“…In the developing mouse forebrain, the expression pattern of CC3 correlates well with terminal deoxynucleotidyl transferase-mediated biotinylated UTP nick end labeling (TUNEL)-positive cells with the majority of CC3 ϩ cells being TUNEL ϩ (Urase et al, 2003). However, there are reports that CC3 staining does not always correlate with apoptosis; yet, in these special cases, the CC3 ϩ cells do not have any other characteristics consistent with apoptosis such as chromosome condensation, DNA fragmentation, or TUNEL staining (Yan et al, 2001;Lossi et al, 2004;Oomman et al, 2004).…”
Section: Increased Apoptosis In the Developing Neuroepithelium Of Shcmentioning
confidence: 99%